KARAKTERISTIK GELOMBANG SIGNIFIKAN DI SELAT KARIMATA DAN LAUT JAWA BERDASARKAN RERATA ANGIN 9 TAHUNAN (2005-2013) - Sigit Wicaksana; Ibnu Sofian; Widodo Pranowo (Journal Omni-Akuatika, 2015)
Karimata strait and the java sea is one of the most densely shipping lanes in the maritime country of Indonesia. Information of a significant wave is needed to safety navigation. The prediction of a significant wave mostly employs the modeling using wind as input data to produce an early warning warning prediction. Characteristic of a significant wave shows the maximum wave height in the strait and the java sea karimata occurs in west monsoon (January) and east season (August) every year. Especially at the peak of west monsoon (January) maximum wave height reach 1.5-3 meters in Karimata Strait, and reach 0.5-2.5 meters in Java Sea. The frequency of significant wave occurences mostly extend until February, where wave height in Java Sea will stay the same (0.5-2.5 meters), while in Karimata Strait is little bit decrease (1-2.5 meters). Recommended to all sea transportation users, in those regions during January and February, to avoid using ship with the hull is less than 3 meters height.Keywords: significant wave characteristic, Karimata Strait, Jawa Sea, Wind, Modeling